Photonuclear production of Yb-175 - Dikiy, N.P.; Dovbnya, A.N.; Krasnoselsky, N.V.; Lyashko, Yu.V.; Medvedeva, E.P.; Medvedev, D.V.; Uvarov, V.L.; Fedorets, I.D. (Вопросы атомной науки и техники, 2017)
The use of photonuclear nanotechnology makes it possible to obtain the ¹⁷⁵Yb isotope with acceptable characteristics without the content of impurities of other isotopes. Irradiation of Yb₂O₃ nanoparticles of a natural isotope composition weight`s 123.5 mg in a mixture with clinoptilolite nanoparticles by bremsstrahlung with an Eₘₐₓ=13.5 MeV was carried out. The prevalence of ¹⁷⁶Yb isotopes is 12.6%. The reaction cross section of ¹⁷⁶Yb(γ,n)¹⁷⁵Yb (T½=100.8 hours) have two maximums at 12.5 and 16 MeV about 350 mbn. After separation of the clinoptilolite particles, the activity of ¹⁷⁵Yb in the theirs was 3.2% of the total activity of the sample for the size of Yb₂O₃ nanoparticles of the 180 nm.